Pendekatan Dilemmas Stories Pada Materi Larutan Penyangga Dengan Metode Think Pair Square (TPSq) - Lisdiana, Hayyun; Hadinugrahaningsih, Tritiyatma; Rahmawati, Yuli (LPPM Universitas Negeri Jakarta, 2023)
The aim of this study is to understand the integration and implication of dilemmas stories approach in learning the buffer solution using the think pair square (TPSq) method related to students‟ soft skills. The subject of this study is XI MIA 5 Senior High School 2 Tangerang, of forty students. This study is conducted from January 2015 until July 2015. This study used interterpretivism paradigm approach using the qualitative method. The focused of this study is the learning process and implication using dilemmas stories in learning the buffer solution using the think pair square (TPSq) method. This study consists two steps: preparation step and execution step. The sources of the data are the interviews with the students, the students reflective journals, and class observation supported by CCVLES questionnaire consisting seven indicators. The data collecting procedure refers to the seven indicators: emotion towards the story, plot, teacher support, teamwork, communication empathy, critical thinking, and contextual chemistry. Quality standards used in this study are credibility by using prolonged engagement, progressive subjectivity, dan member checking. Based on this study, it is found that the students are interested and motivated to learn chemistry through stories. They also learn to work in team, learn to appreciate other‟s opinions, and learn to solve problems in chemistry by thinking critically. Confidence, responsibility, curiosity, and creativity can be seen through the posters and videos created by the students in the final step of the learning. Dilemmas Stories can be used as an alternative in learning the buffer solution.